2018
DOI: 10.1111/wre.12343
|View full text |Cite
|
Sign up to set email alerts
|

Variability in seedling emergence for European and North American populations ofAbutilon theophrasti

Abstract: Summary Abutilon theophrasti is a weed that is spreading worldwide and that has had to adapt to different combinations of environmental conditions. Wide interpopulation variability has been reported regarding dormancy and germination. This variability, controlled by the interaction of genetic diversity and maternal effect, could hinder the adoption of Integrated Weed Management (IWM) tools. A collaborative project was conducted to compare emergence dynamics of 12 European and North American populations under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The prediction of A. retroflexus and S. pumila using the AltertInf model with its original parameters is unfortunately impossible, even in irrigated maize crops, since the T b values of Croatian populations differ statistically from those of the Italian populations present in the hydrothermal model. This variability in germination parameters has also been documented in previous studies and is usually explained as an adaptation process of weed species to local climate conditions [13,36]. The annual air temperature in Zagreb is, on average, lower than that in Padova.…”
Section: Discussionsupporting
confidence: 74%
“…The prediction of A. retroflexus and S. pumila using the AltertInf model with its original parameters is unfortunately impossible, even in irrigated maize crops, since the T b values of Croatian populations differ statistically from those of the Italian populations present in the hydrothermal model. This variability in germination parameters has also been documented in previous studies and is usually explained as an adaptation process of weed species to local climate conditions [13,36]. The annual air temperature in Zagreb is, on average, lower than that in Padova.…”
Section: Discussionsupporting
confidence: 74%
“…Prediction of A. retroflexus and S. pumila by AltertInf model with its original parameters is unfortunately impossible, even in irrigated maize crops, since the Tb values differ statistically with those Italian presents in the hydrothermal model. This variability in germination parameters has also been documented in previous studies and usually explained as adaptation process of weed species to local climate conditions [13,36]. The annual air temperature in Zagreb is on average lower than those in Padova (Table 1).…”
Section: Discussionsupporting
confidence: 80%
“…The found variability in seed traits between C. edulis populations may have important implications for this invasive species management. The work developed by Loddo et al (2019) that evaluated variability in the invasive species Abutilon theophrasti seed traits demonstrated that achieving a better knowledge of interpopulation variability can allow specific control strategies to be designed, facilitating the development of new management tools. Likewise, germination rates of the Alexandra palm were found to potentially better inform of management strategies for the control of this species (Wen 2019).…”
Section: Geographic Intraspecific Variation In Invasive Species: Management Implicationsmentioning
confidence: 99%